The Influence of Adolescent Integrated Helath Center on Adolescent Reproductive Health Status in Junior High School 3 Pekuncen, Banyumas District: Pengaruh Posyandu Remaja terhadap Status Kesehatan Reproduksi Remaja di SMP Negeri 3 Pekuncen, Kabupaten Banyumas - Zahra, Fadhillah Anindya; Kusuma, Aditia Darma; Intan, Seviana Ratna; Mentari, Neisha; Aditia, Putra Lesmana; Efa, E; Fitriyani, F (Prosiding University Research Colloquium, 2024)
Adolescents in Indonesia face various challenges during the transition from childhood to adulthood, including the risk of irresponsible sexual behavior. This article discusses the impact of lack of knowledge about reproductive health on adolescents, with a focus on unwanted pregnancies, abortion, and nutritional problems. Data shows a high percentage of adolescents who engage in premarital sexual intercourse and experience unwanted pregnancies. The government seeks to improve adolescent knowledge through the adolescent posyandu program. The research method included a pre-experiment with pre-test and post-test to evaluate the impact of posyandu activities. The results showed an increase in adolescents' knowledge about reproductive health, a decrease in the level of anemia, and an improvement in nutritional status after participating in adolescent posyandu. Prevention efforts involve education, information, and active participation of adolescents as subjects. In conclusion, adolescent posyandu can be an effective strategy in improving adolescent reproductive health and nutrition in Indonesia.